Identification of fertility restorer and sterility maintainer lines in chilli (Capsicum annuum L.) - S K Rao, B V Tembhurne (Journal of Spices and Aromatic Crops, 2012)
Three cytoplasmic geneic male sterile lines of chilli (Capsicum annuum L.) namely, JNKVVA1, ACBGA1 and ACBGA2 showed 100% male sterility when tested with 1% acetocarmine solution. Among the 50 chilli lines crossed with the three male sterile lines, 36 lines were stable for fertility restoration (Rf) while, two lines namely, AVNPC131 and X235 were identified as sterility maintainers (rf).